Facile synthesis of pristine FeS2 microflowers and hybrid rGO-FeS2 microsphere electrode materials for high performance symmetric capacitors - Balakrishnan, Balamuralitharan; Balasingam, Suresh Kannan; Sivalingam Nallathambi, Karthick; Ramadoss, Ananthakumar; Kundu, Manab; Bak, Jin Soo; Cho, In Ho; Kandasamy, Prabakar; Jun, Yongseok; Kim, Hee-Je (Journal of industrial and engineering chemistry (Seoul, Korea), 2019)
[Display omitted] •FeS2 flower-like microspheres and rGO-FeS2 composites material was successfully synthesized by facile hydrothermal route.•The rGO-FeS2 composite electrode exhibit excellent electrochemical performances.•Improved penetration of Na2SO4 electrolyte ions into the rGO-FeS2 composite electrode was observed.•rGO-FeS2 composite electrode shows an capacity retention of 90% over 10,000 cycles at 0.3mAcm−2. Iron pyrite (FeS2) is an interesting mineral in the transition metal dichalcogenide group due to its high abundance in the earth’s crust which can be used for various electrochemical energy storage applications, such as batteries and supercapacitors; however, it suffers from low rate capability and poor cycle performance, which hampers its use from large-scale commercial applications. In the present study, iron disulfide microspheres anchored onto a reduced graphene oxide matrix (rGO-FeS2 hybrid) were grown using a superficial hydrothermal method. For comparison, rGO-free iron disulfide material was synthesized under the same hydrothermal conditions, and uniformly distributed FeS2 micro-size flowers were formed. The energy storage capacity of both electroactive materials (FeS2 and rGO-FeS2 hybrid material) was tested for supercapacitor applications in a symmetric cell configuration. The pristine FeS2 microflower electrode exhibited an areal capacitance of 70.98mFcm−2 at 5mVs−1. On the other hand, the rGO-FeS2 hybrid microsphere electrode exhibited an enhanced areal capacitance of 112.41mF cm−2 at the same scan rate with an excellent capacitance retention of 90% over 10,000 cycles. The improved electrochemical performance of the rGO-FeS2 hybrid material is due mainly to its improved electrical conductivity, high surface area indicating an enhanced electron, and ion transfer mechanism. This study suggests that the rGO-FeS2 hybrid electrode material has potential applications in energy storage devices.